Sektor Pelayanan Publik Sebagai Sarana Korupsi di Kota Medan - Nasution, Rasina Padeni; Batuabara, Indah Sakinah; Rahma, Annisa Aulia; Aila, Nurul; Amaliah, Rizky; Butarbutar, Rini Andriani (Ikatan Dai Indonesia, 2023)
The purpose of this investigation is to ascertain the scope of the Ombudsman's function as a state institution with the authority to oversee the implementation of public services organized by state and government administrators. These public services include those held by State-Owned Enterprises, Regional-Owned Enterprises, and State-Owned Legal Entities, as well as private entities or individuals tasked with managing specific public services in the Medan City region.An interview and observation-based qualitative descriptive research approach was utilized in this study.